Cryosurgery in the treatment of oro-facial lesions - Ashok Bansal; Shivani Jain; Shipra Gupta (Wolters Kluwer Medknow Publications, 2012)
Cryosurgery is a therapeutical method that uses freezing to obtain a tissue inflammatory and/or a destructive response. It has been successfully used for many cutaneous conditions. Its use is increasing for several conditions in the oral cavity. The oral mucosa, because of its characteristics of humidity and smoothness, is an ideal site for this technique. It shows a very good esthetic result and it may be either the first choice or an alternative option to conventional surgery. This article strives to review the modus operandi of cryosurgical instruments, the various indications, limitations and advantages of cryosurgery in the treatment of oral lesions.